Del Mandubracius del De Bello Gallico de C. Julio César al Endriago del Amadis de Gaula (II parte) - Suárez Pallasá, Aquilino (1996)
Fil: Suárez Pallasá, Aquilino. Pontificia Universidad Católica Argentina; Argentina